Pengembangan Model Latihan Teknik Hakdari Soegi pada Atlet Poomsae Taekwondo Prabu - Shinta Azzahra Jamaludin Putri; Fahmy Fachrezzy; Uzizatun Maslikah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This study aims to develop a Hakdari Soegi Technique Training Model for Poomsae Taekwondo Pabu Athletes. In accordance with the objectives used by the researcher, namely up to five steps of research or up to the expert validation stage where this research uses the ADDIE research and development (R&D) research method. to get the right model in accordance with the purpose of developing a training model based on Hakdari Soegi's technical theory in the taekwondo sport in the poomsae number studied. After researching, then the researcher made a book on the Hakdari Soegi Technique Training Model on Poomsae Taekwondo Prabu Athletes, followed by the validation process stage carried out by three Taekwondo expert judgements. In the book Hakdari Soegi Technique Training Model on Poomsae Taekwondo Prabu Athletes, the researcher explained, made a design, made twelve training models developed from the Hakdari Soegi technique using tools, in order to provide benefits for Poomsae Prabu athletes and improve the Hakdari Soegi technique so that the performance of athletes in performing poomsae movements can maximize and build the minds of athletes that having good technical skills is very important, especially in doing poomsae movements because it affects the assessment during the match. Conclusion in the book Hakdari Soegi Technique Training Model on Poomsae Taekwondo Prabu Athletes, the Hakdari Soegi technique training model on Poomsae Taekwondo Prabu Athletes is worthy of being used as a training program in taekwondo training. .